MtDNA depletion influences the transition of CD44 subtypes in human prostate cancer DU145 cells - Xiaoran Li; Mantas Grigalavicius; Yaqing Li; Xiaoli Li; Yali Zhong; Ruixia Huang; Dandan Yu; Viktor Berge; Mariusz Adam Goscinski; Gunnar Kvalheim; Jahn M Nesland; Zhenhe Suo (Tumor Biology, 2017)
Our earlier study revealed that long-term ethidium bromide application causes mitochondrial DNA depletion in human prostate cancer DU145 cell line (DU145 MtDP ), and this DU145 MtDP subline appears to have expanded CD44 Bright cell population than its parental wild type DU145 cells (DU145 WT ). Increasing evidence suggests that CD44 Bright cells are highly cancer stem cell like, but it is not clear about their dynamic transition between CD44 Dim and CD44 Bright phenotypes in prostate cancer cells, and how it is affected by mitochondrial DNA depletion. To address these questions, four cell subpopulations were isolated from both DU145 WT and DU145 MtDP cell lines based on their CD44 expression level and mitochondrial membrane potential. The cell motility and colony formation capability of the fluorescence activated cell sorting–sorted cell subpopulations were further examined. It was discovered in the DU145 WT cells that CD44 Dim cells could transit into both CD44 Dim and CD44 Bright phenotypes and that CD44 Bright cells were prone to sustain their CD44 Bright phenotype as renewal. However, such transition principle was altered in the DU145 MtDP cells, in which CD44 Bright cells showed similar capability to sustain a CD44 Bright phenotype, while the transition of CD44 Dim cells to CD44 Bright were suppressed. It is concluded that mitochondrial DNA depletion in the human prostate cancer DU145 cells influences their renewal and CD44 subphenotype transition. Such alterations may be the driving force for the enrichment of CD44 Bright DU145 cells after the mitochondrial DNA depletion, although the molecular mechanisms remain unclear.